Evaluation of in vitro Vibrio static activity of Shewanella algae isolated from healthy Penaeus monodon - Shakibazadeh, Shahram; Saad, Che Roos; Christianus, Annie; Kamarudin, Mohd Salleh; Sijam, Kamaruzaman; Shamsudin, Mariana Nor; Neela, Vasantha Kumari (Academic Journals, 2008)
To conquer disease problem in shrimp industries, probiotic biocontrol is a well known remedy now. The antagonistic ability of separated isolates from different parts of juvenile Penaeus monodon were screened against shrimp Vibrio pathogens; Vibrio parahaemolyticus and Vibrio alginolyticus. The most antagonistic effect was observed for an isolate that was primarily identified as Shewanella algae using conventional methods followed by Biolog microlog software. Since production of antagonistic agents rely on cultural conditions, antagonistic ability of candidate probioic against the mentioned Vibrios was assessed using Response Surface Methodology, with central composite design in which four independents variables were assumed: temperature (10 - 50°C), pH (6 -10), NaCl concentration (0 - 50%) and time (12 – 60 h). The coefficients of multiple determinations (R2), for the responses of antagonistic effect of S. algae against V. parahaemolyticus and V. alginolyticus values were 0.807 and 0.805, respectively. Concentration of the NaCl exhibited least influence on the antibacterial effect of candidate probiotic while the other independent variables exhibited different degree of affect. The candidate probiotic revealed a reasonable antibacterial response in quite a wide range of temperature and pH in which the maximum levels were in the same range of optimum shrimp culture.